Sound transmission through baffled multilayered curved shells using a transfer matrix method - Parrinello, A.; Belgacem, W.; Ghinet, S.; Atalla, N. (Frontiers in Mechanical Engineering, 2022)
This paper discusses the use of a transfer matrix method for predicting the acoustic behavior of baffled curved shells consisting of a generic arrangement of homogeneous and heterogeneous periodic layers of various nature (fluid, solid, poroelastic). The through-radius transfer matrix of a layer characterized by cylindrical periodicity is derived by manipulating the dynamic stiffness matrix related to a finite element model of a representative unit cell. The proposed technique is equally appealing for homogeneous layers since few elements are needed in this case as compared to conventional finite element approaches. With the proposed framework, different layers can be combined to form multilayered shells and the related acoustic radiation or transmission due to a plane wave or a diffuse acoustic field can be assessed. The blocked pressure field due to an incident plane wave is defined by taking into account the infinite rigid baffle by means of a two-dimensional boundary element model. Analytical expressions for the cylindrical acoustic impedances are utilized to define the coupling with the bounding fluid media. Furthermore, a one-dimensional windowing technique is adopted to account for the finite length of the shells. The proposed approach is validated by systematic comparison with a full finite-boundary element method.